Analysis of Elements of Abuse of Authority in Corruption Crimes by the Head of the PUPR Office (Study of Decision Number 18/Pid.Sus-TPK/2025/PN.Tjk) - Ani; Puspita Meisy Astrini; Ravelina Oktavia; Tian Terina (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the application of the element of abuse of authority in criminal acts of corruption based on Article 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, with a focus on Decision Number 18/Pid.Sus-TPK/2025/PN Tjk against the Defendant Ir. Jalaludin MP as Head of the Public Works and Public Housing Agency of West Pesisir Regency. The issues examined include the application of the element of abuse of authority in Article 3 of the Anti-Corruption Law, the fulfillment of this element in the Defendant's actions, and the basis for the judge's consideration in handing down the verdict in relation to the principle of substantive justice. This study uses a normative juridical method with a case approach and a statute approach, analyzing secondary data in the form of court decisions, laws and regulations, and legal literature through qualitative analysis techniques. The results of the study show that the Panel of Judges proved that the Defendant abused his authority as a Budget User by approving the disbursement of project funds that did not comply with the contract specifications, resulting in state losses of IDR 1,887,218,440.32. The judges' considerations used a formalistic approach by proving all elements of Article 3 cumulatively, but did not sufficiently explore the dimension of abuse of authority from the perspective of state administrative law. This verdict confirms that public office creates legal obligations which, if violated for personal gain, constitute an abuse of authority that is detrimental to state finances. Keywords: Abuse of Authority, Corruption Offenses, State Financial Losses